Regulation Problems of Case Settlement using ECourts in Indonesia Courts - Irham Rahman; Djoko Heroe Soewono (Fakultas Hukum Universitas Kadiri, 2022)
ABSTRACT The Supreme Court Regulation No. 1 of 2019 concerning the Electronic Administration of Cases and Assembly is a breakthrough in the field of law to keep up with the development of information and technology. There are more incoming cases than solved cases. The implementation of e-court in solving cases must be in line and supportive with formal law principles. This study uses a normative juridical method using the statute approach and case approach. Service improvement and settlement of cases must is the obligations of judicial power, supported by the electronic media. E-Court has a role in creating a quick, effective and substantial justice system in settlement of cases under fairness principle and certainty of law. Keywords: Regulation, E-Courts, Case, Indonesia Courts